2013
DOI: 10.1159/000343672
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Site-Specific Proteome Changes Induced by Neuronal P60TRP Expression

Abstract: p60 transcription regulator protein (p60TRP) facilitates the processing of the amyloid precursor protein towards the non-amyloidogenic pathway by inhibiting the β-secretase action. This protein was initially identified to be downregulated in the temporal lobe of brains from Alzheimer's disease patients. p60TRP is one of the G-protein-coupled receptor (GPCR)-associated proteins which directly influences the signalling capacity of GPCRs. In the present study, we investigated the brain-region-specific proteome pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 112 publications
1
6
0
Order By: Relevance
“…First, the significantly altered proteins in rpAD plaques were compared to our database of AD associated proteins identified in previous proteomic studies[1, 2, 4, 11, 13, 14, 22, 3133, 36, 37, 43, 45, 50, 54, 55, 66, 77, 78, 82, 89, 90, 96]. In this database we annotated proteins as up-regulated in AD, down-regulated in AD and proteins that are enriched in plaques or tangles (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the significantly altered proteins in rpAD plaques were compared to our database of AD associated proteins identified in previous proteomic studies[1, 2, 4, 11, 13, 14, 22, 3133, 36, 37, 43, 45, 50, 54, 55, 66, 77, 78, 82, 89, 90, 96]. In this database we annotated proteins as up-regulated in AD, down-regulated in AD and proteins that are enriched in plaques or tangles (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…This database combined the results from studies that identified proteins in neurofibrillary tangles[50, 66, 82], proteins enriched in plaques[32, 43], proteins that had significantly altered expression in various regions and/or fractions of AD brains in comparison to control brains and proteins that contained the keyword “Alzheimer” in the Uniprot human database[1, 2, 4, 11, 13, 14, 22, 3133, 36, 37, 45, 54, 55, 77, 78, 89, 90, 96]. Protein groups identified in rpAD and sAD plaques were screened against this database to determine how many of the proteins identified in this study have been previously associated with AD pathology.…”
Section: Methodsmentioning
confidence: 99%
“…A similar method was also used to determine if the proteins that were detected in our neuronal sample had been previously associated with AD. A second compilation of AD-associated proteins was established that combined the results from studies that identified proteins in neurofibrillary tangles 7 8 9 , proteins up-regulated in plaques 14 , proteins that had significantly altered expression in various regions and/or fractions of the AD brain in comparison to control brains 10 15 16 17 18 19 20 21 22 23 24 25 and all proteins that contained the keyword “Alzheimer” in the UniProt human database (accessed 9/4/14). It was found that 209 of our total identified 399 proteins (52%) had previously been associated with AD ( supplementary Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that decreased KCC2 expression has been observed in the hippocampus AD11 mice which express an anti-NGF antibody and develop AD-like hallmarks including amyloid deposits 65 . In addition, mice overexpressing p60TRP, a G-protein coupled receptor known to promote non-amyloidogenic processing of APP, bare an increase in KCC2 expression 66 . Given these observations, it would be interesting to investigate whether these KCC2 expression changes could be linked to a dysregulation in APP processing.…”
Section: Discussionmentioning
confidence: 99%